2021
DOI: 10.1186/s12866-021-02294-z
|View full text |Cite
|
Sign up to set email alerts
|

Induction of amylase and protease as antibiofilm agents by starch, casein, and yeast extract in Arthrobacter sp. CW01

Abstract: Background In unfavourable environment, such as nutrient limitation, some bacteria encased themselves into a three dimensional polymer matrix called biofilm. The majority of microbial infections in human are biofilm related, including chronic lung, wound, and ear infections. The matrix of biofilm which consists of extracellular polymeric substances (EPS) causes bacterial colonization on medical implanted device in patients, such as catheter and lead to patient’s death. Biofilm infections are ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…According to genome sequencing studies, certain strains of bacteria in the genus Arthrobacter exhibit the genes encoding proteolytic, lipolytic, and glycolytic pathways [ 115 , 116 , 117 ]. These revelations confirm the results of several studies related to such enzyme-producing Arthrobacter bacteria [ 118 , 119 ]. Proteolysis, lipolysis, and glycolysis are normally considered the important elements of biochemical change in milk during fermentation leading to the nutritional value of final products.…”
Section: Significance Of Arthrobacter Spp In the D...supporting
confidence: 89%
“…According to genome sequencing studies, certain strains of bacteria in the genus Arthrobacter exhibit the genes encoding proteolytic, lipolytic, and glycolytic pathways [ 115 , 116 , 117 ]. These revelations confirm the results of several studies related to such enzyme-producing Arthrobacter bacteria [ 118 , 119 ]. Proteolysis, lipolysis, and glycolysis are normally considered the important elements of biochemical change in milk during fermentation leading to the nutritional value of final products.…”
Section: Significance Of Arthrobacter Spp In the D...supporting
confidence: 89%
“…The EPSs thus shield bacteria present in the biofilm from antibiotics, while planktonic cells do not receive this protection [ 33 ]. Extracellular proteins [ 34 ] and eDNA [ 35 ] play critical roles in biofilm formation, and eDNA is an anionic macromolecule that can chelate cations [ 36 ]. Therefore, DNase I and proteinase K were used to reduce these matrix components of the V. parahaemolyticus biofilm and the antibiotic resistance of cells was measured in this depleted environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, lowtemperature active amylase from Arthrobacter sp. is useful in detergent formulation, and Solihin et al (2021) reported a strain that produces synergistic antibiofilm efficiency with proteases. In their study, Han et al (2021) revealed that the genus Arthrobacter consists of bacteria commonly found in cold environments.…”
Section: Phylogenetic Tree and Evaluationmentioning
confidence: 99%